Relationship between Health Problem and Suicide Ideation among Correctional Officers - Razali Othman, Mohd; Abdullah, Suraida; Mohd Taib, Tasnim; Mazlina Ghazali, Nor; Fatihah Abdullah Bandar, Nur (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relationship between health problems and suicidal ideation amongst 157 correctional officers from three institutions of prison in Malaysia. The participants completed an online assessment to identify their problems and rule out suicidal ideation. The existence and severity of health problems were assessed by using the Employee Needs Assessment Inventory (ENAI), while the Interpersonal Needs Questionnaire (INQ) evaluates the presence of suicidal ideation. Overall, health problems were found to be positively related to suicide ideation (r=.210**, p